食道がん患者における術前補助化学療法と手術療法に伴うサルコペニア関連指標の推移：単一施設の前向き観察研究 - 深田 順子; 鎌倉 やよい; 山口 真澄; 渡邉 直美; 西岡 裕子; 宮谷 美智子; 髙津 淳; 前田 明弘; 南谷 志野; 安部 哲也 (日本看護科学会誌, 2024)
要旨　目的：周術期におけるサルコペニア予防プログラムを検討するために，食道がん患者における術前補助化学療法（NAC）前・後，術前・後のサルコペニア関連指標および影響要因の推移と，術後骨格筋量指数（SMI）の影響要因を明らかにする．　方法：対象は食道がんでNAC・右開胸開腹食道切除術予定患者27名．NAC前・後，術前・術後（術後第6病日）にSMI，握力，歩行速度，舌口唇運動機能等を測定し，統計解析を行った．　結果：対象は男性23名，平均年齢64.5歳．術後のサルコペニアの発症率は33.3％，NAC前・後，術前と比較し術後の両下肢の筋肉量が有意に低下し，NAC前・後と比較して術後の/pa/，/ta/，/ka/の回数/秒が有意に減少した．術後のSMIを従属変数とした重回帰分析の結果，NAC前のSMI，レジメン，性が有意に影響した．　結論：NAC前から下肢や口唇・舌の運動等の必要性が示唆された． 　Purpose: The aim of the study was to examine the sarcopenia prevention programs in the perioperative period. We examined changes in sarcopenia-related indices and associated factors before and after neoadjuvant chemotherapy(NAC) and surgery, as well as factors that affect postoperative skeletal muscle mass index(SMI) in esophageal cancer patients.　Methods: The subjects were 27 patients with esophageal cancer expected to undergo subtotal thoracic esophagectomy by right thoracolaparotomy following NAC. SMI, grip strength, walking speed, and oral diadochokinesis were evaluated before and after NAC, before surgery, and on the 6th postoperative day. Changes in the data and factors that affect SMI after surgery were statistically analyzed.　Results: The subjects included 23 males with a mean age of 64.5 years, the incidence of postoperative sarcopenia was 33.3%. Muscle mass was significantly reduced in the bilateral lower limbs after surgery compared with before and after NAC and before surgery. The number of pa/ ta/ ka/ times/second was significantly reduced after surgery compared with before and after NAC. Multiple regression analysis using the postoperative SMI as the dependent variable showed that SMI before NAC, regimen of chemotherapy(docetaxel, CDDP, 5FU), and male sex significantly affected SMI after surgery.　Conclusion: The necessity of exercising the lower limbs, lips, and tongue from before NAC was suggested.